Pulmonary diffusion capacity predicts major complications after esophagectomy for patients with esophageal cancer. Issue 3 (17th September 2018) - Goense, L; Meziani, J; Bülbül, M; Braithwaite, S A; van Hillegersberg, R; Ruurda, J P
Summary: A reduced forced expiratory volume in one second (FEV1 ) is a well-recognized risk factor for complications after esophagectomy. Lung diffusing capacity for carbon monoxide (DLCO) is not routinely integrated in the risk assessment of esophagectomy. The aim of this study is to evaluate the association of preoperative pulmonary function tests with major postoperative complications after esophagectomy for cancer. In order to achieve this aim, 459 patients with newly diagnosed esophageal cancer who underwent elective transthoracic ( n  = 352) or transhiatal ( n  = 107) surgical resection of the esophagus with cervical anastomosis between 2003 and 2015 were analyzed. Multivariable logistic regression analysis was performed to assess the association of preoperative pulmonary function tests (expressed as % of predicted) with major complications after esophagectomy, adjusted for previously identified predictors. Major complications were defined as Clavien-Dindo grade IIIb or higher. Of the 459 included patients, 114 (24.8%) developed major complications. In univariable analysis FEV1, forced vital capacity (FVC), vital capacity (VC), and DLCO were associated with major complications. After adjusting each pulmonary function test for age, American Society of Anesthesiologists (ASA) score, cardiac comorbidity, diabetes mellitus, peripheral vascular disease, and surgical approach, FVC (OR: 1.24 per 10% decrease; 95% CI: 1.06–1.45; P  = 0.004), VC (OR: 1.19 per 10% decrease; 95% CI: 1.02–1.39; P  = 0.025) and DLCO (OR: 1.16 per 10% decrease; 95%CI: 1.02–1.33; P  = 0.025) remained predictive factors for major surgical complications. In multivariable analysis in which all pulmonary functions tests were combined, DLCO was the strongest predictor of major complications (OR: 1.14 per 10% increase; 95% CI: 1.01–1.30; P  = 0.046). The ideal cut-off for DLCO% of predicted was determined at <84% (OR: 1.97; 95% CI: 1.28–3.03; P  = 0.002). These data indicate that DLCO is an independent predictor of major complications after esophagectomy for cancer. This pulmonary function test deserves greater consideration in prediction research of major complications after esophagectomy.